ҒАРБ МАМЛАКАТЛАРИ МЕДИАСИДА ХОРИЖИЙ МАМЛАКАТ (ҲУДУД) ИМИЖИГА НИСБАТАН МУНОСАБАТЛАРНИНГ САҚЛАНИБ ҚОЛИШИ МУАММОСИ - Алимов, Б. (SCIENCE and SOCIETY, 2020)
This article analyzes the role of foreign media in creating the image of the country. The image of any state has an unchanging, stable character, which is formed in the minds of the peoples of the world for many years, sometimes centuries. It is not easy for it to appear in a certain context and then drastically change the image that remains in people’s minds.